(untitled) (International Journal of Engineering and Computer Science, 2014)
Semantic web service composition constructs the OWL-S composite process automatically based on AI planning techniques. The need for verification of the service composition plan is essential as it is error prone. Colored Petri Nets had been proposed for verification due to its graphical, contains formal semantics and allows various analyses. The verification is done by constructing a CPN for an online book purchasing scenario using CPN tools and analyzing it through simulation. “CPN Tools” is the tool used to simulate the entire process flow and provide the statistics about liveliness, fairness and boundedness properties. An online book purchase has been considered as a case study.